Constituents in tobacco and smoke emissions from Canadian cigarettes. (2nd September 2008) - Hammond, D; O'Connor, R J
Abstract : Background: There is relatively little information available about the chemical constituents of tobacco and individual toxic emissions from cigarettes and other tobacco products. Objective: To characterise 21 constituents in whole tobacco and 41 constituents in the smoke emissions of Canadian cigarettes, as well as to compare differences between domestic and imported brands. Methods: All data were released as part of Canada's Tobacco Reporting Regulations. Data are reported for 247 brands tested in 2004. Results: The results indicate significant differences in the constituent levels of domestic and imported cigarette tobacco. Levels of ammonia compounds were significantly higher in imported "US blended" tobacco compared to domestically manufactured brands. Toxic emissions for tobacco-specific nitrosamines were significantly higher for imported cigarettes under both the ISO and Canadian Intense testing methods; however domestic cigarettes had higher levels of other toxic constituents, including benzo[a]pyrene. The findings also highlight the extent to which nicotine, heavy metals and tobacco-specific nitrosamines are "transferred" from the whole tobacco to the smoke. Conclusions: The findings illustrate important differences between domestically manufactured Virginia flue-cured cigarettes and imported US blended cigarettes. Although the findings suggest that domestic cigarettes had lower levels of constituents such as ammonia, which are associated with increased "additives", Canadian cigarettes were by no means "additive-free." Overall, these findings provide important benchmarks for making historical and international comparisons across brands on key constituents.